The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1590/s1984-82502016000200009
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of orally disintegrating clopidogrel tablets

Abstract: Recent advances in drug delivery systems have aimed to achieve better patient compliance. One of these advances is the formulation of orally disintegrating tablets (ODTs) that dissolve instantaneously, releasing drugs within a few seconds without the need of water. The main objective of this paper was to prepare and develop ODTs of clopidogrel. The ODTs were prepared by direct compression. The effect of three superdisintegrants, namely crospovidone, croscarmellose sodium, and sodium starch glycolate, using thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
(4 reference statements)
2
11
0
Order By: Relevance
“…This may be due to the conversion of the hydrochloride salt to its less soluble free base [15]. Similar pH dependent Meclizine HCl release was also observed by Mahrous et al [2]. …”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This may be due to the conversion of the hydrochloride salt to its less soluble free base [15]. Similar pH dependent Meclizine HCl release was also observed by Mahrous et al [2]. …”
Section: Discussionsupporting
confidence: 57%
“…It is also indicated for pruritus, anaphylactic reactions and vertigo associated with diseases affecting the vestibular system (e.g., Meniere disease, labyrinthitis) [1, 2]. It is more frequently prescribed because of fewer adverse effects [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disintegration time was determined in phosphate buffer pH 6.8 using tablet disintegration test apparatus (Electrolab, ED-21, Mumbai, India) on six tablets according to the USP30-NF25 requirements for immediate release tablets. The tablet was put in 500 ml phosphate buffer pH 6.8 and the time taken for the tablet to disintegrate into fine particles was calculated (Mahrous et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Mahrous et al, studied the effect of three superdisintegrants; crospovidone, croscarmellose sodium, and sodium starch glycolate using ODTs of Clopidrogel, they reported that in-vitro disintegration tests and in vitro drug release, tablets showed a fast disintegration within seconds at pH 6.8 and more than 90% of the drug was released within 5 min in acidic medium 18 . Results obtained for the similarity factor at 6 h of release revealed differences in the release profile of the assayed formulations compared to the reference product Table 4.…”
Section: Fig 4: Release Profile Of Nifedipine At 12 H Of Release Of mentioning
confidence: 99%